Quality and Safety of Green Mussel (Perna viridis) at Ketapang, Tangerang Regency, Indonesia - Permadi Aef; Asriani; Yuniarti Tatty; Sumandiarsa I Ketut; Budi Purnamasari Heny; Dharmayanti Niken; Zachro Nurbani Siti; Sayuti Mohammad; Salampessy Randi B.S.; Sipahutar Yuliati H.; Ruminta Siregar Resmi; Ayu Afifah Rufnia; et al. (BIO Web of Conferences)
This study aimed to determine the chemical and microbiological qualities of raw green mussels of different sizes in Ketapang Village, Tangerang Regency, Indonesia. The research method used was a single-factor treatment design of green mussel size with small (51-60 mm), medium (61-70 mm), and large (71–80 mm) sizes with environmental design and Complete Random Design. The parameters used were the content of heavy metals Pb, proximate, and microbiology. ICP-MS was used for heavy metal testing. The method of analyzing the proximate content and microbiology refers to the Indonesian National Standard (SNI). The results of the study showed that green mussels with shell sizes of 51-60 mm and 71-80 mm significantly affected the lead (Pb) content. The different sizes of green mussel shells significantly affected the protein and fat content. As for the carbohydrate content, a significant difference was only shown by green mussels with shell sizes 51-60 mm and 71-80 mm. The results of microbiological tests showed that the Total Plate Count in green mussels did not exceed the SNI, the Escherichia coli content exceeded the SNI limit, and there were green mussel samples that were positive for Salmonella and Vibrio parahaemolyticus.